Implementasi Manajemen dan Digitalisasi Perpustakaan dalam Meningkatkan Layanan Pendidikan di SDN Manukan Wetan 1/114 - Nengrum, Felis Tria; Ramadhani, Fitria Rizky; Vrachmadhani, Viojezsha Valibra; Herdyastuti, Jofita Tri; Krisnawati, Eka Putri; Valentiara, Nadhea Kusuma; Firman, Muhammad Farel Maulana; Fitria, Rezki Nurma (Lembaga Yasin AlSys, 2025)
The issue of limited literacy access and the quality of library services in elementary schools presents a significant challenge to improving educational quality. This study aims to analyze the implementation of library management and digitalization in supporting educational services at SDN Manukan Wetan 1/114 Surabaya. A qualitative case study approach was used, with data collected through interviews, observation, and documentation. The findings show that the school library has implemented structured management, including an organizational structure, the Dewey Decimal Classification system, and the use of digital applications such as INLISLite 3.2, with further development plans involving the DIGIDO platform. Despite challenges such as the shortage of professional librarians and concerns over digital copyright, several literacy services continue to operate, including mandatory reading visits, storytelling activities, and mobile library services. These findings indicate that effective library management and targeted digitalization can enhance reading interest and improve the efficiency of information services in elementary school settings. The implications of this study highlight the importance of technological infrastructure support, library staff training, and strengthened copyright regulations to optimize the role of digital libraries as a key component in foundational literacy education.